Knowledge-sharing and collaborative behaviour: An empirical study on a Portuguese higher education institution - Chedid, Marcello (2019)
Collaboration has been considered a way to address the challenges of the 21st century, fostering the necessary innovation, growth and productivity for all parties involved. Several studies reveal that collaboration can be strongly influenced by knowledge sharing. The literature suggests that this topic is quite relevant and that there is an evident lack of empirical studies that properly investigate the relationship between knowledge-sharing and collaborative behaviour in Higher Education Institutions (HEIs). In this context, the purpose of this work is to examine whether knowledge-sharing intention has a positive relationship with collaborative behaviour among professors and researchers in a public Portuguese HEI, taking into account other constructs that can have effect on the knowledge-sharing intention. In order to reach this objective, a conceptual research model was developed based on the theory of reasoned action. The empirical study was conducted based on a questionnaire, and the data analysis was performed using partial least squares. The results indicate that intrinsic motivation and networking are the factors that positively affect the attitude towards knowledge sharing. Nevertheless, it is concluded that trust is the variable that more strongly affects the knowledge-sharing intention. Finally, the study identified that knowledge-sharing intention has a positive influence in collaborative behaviour. It is considered that this study can contribute to support institutions’ management in defining strategies and developing actions in order to promote an organisational culture based on knowledge management that significantly leads to knowledge-sharing and collaboration relationships.